Aeroelastic numerical simulation of a magnetically levitated horizontal axis wind turbine. (February 2021) - Fekry, M.; Yoshida, S.
Highlights: Providing an aeroelastic numerical simulation of the magnetically levitated horizontal axis wind turbine. Adding five degrees of freedom to the OpenFAST which is NREL's primary aeroelastic computer-aided engineering tool for simulating the coupled dynamic response of wind turbines. Developing a general code for the application of magnetic bearings for the wind turbines. Enhancing the tower fore-aft deflection and increasing the reliability of wind turbines. Abstract: This paper presents mathematical modeling of direct drive wind turbines with a three-point suspension magnetically levitated drivetrain. An aeroelastic numerical simulation is performed using OpenFAST software. A 10 kw small wind research turbine (SWRT) is chosen as a preliminary step in the development of a general reliable magnetically levitated drivetrain model for wind turbine (WT) simulations. This model adds an additional five degrees of freedom (DOF) to the current version of OpenFAST V2.1.0 and aims to provide more extensive studies of the application of magnetic bearing (MB) on WTs, which is the main objective of this work. The analytical design of the magnetic levitation system for WTs under study is considered. The dynamic equations of OpenFAST are redeveloped using Kane's method for the flexible multi-body motion to include the levitated shaft dynamics. The inherent insatiability of the MB system is overcome with a robust Q-parameter model-based controller. The new dynamic equations of the MB are verified under different wind scenarios to prove the ability of MB to compensate for different aerodynamic and gravitational loads. The simulation results show that MB technology is a promising approach that can help to mitigate the WT's vibrations and solve the current mechanical bearing problems.